Antimicrobial resistance and gallbladder carriage of Salmonella Typhi and Salmonella Paratyphi A in Kathmandu, Nepal - Dongol, S (2013)
Enteric fever remains the most common febrile illness in urban Nepal. Some individuals may have recurrent infection and some may even progress to become long term chronic carriers. The aim of this thesis was to investigate the rate and factors leading to relapse with typhoid fever in patients who were enrolled in clinical treatment trials for acute enteric fever. The results show that relapses in enteric fever is a common complication and is more likely to be associated with the treatment antimicrobial, cefixime. Gallbladder carriage of invasive Salmonella is considered fundamental in sustaining enteric fever transmission as humans are the only known natural host. This thesis, therefore, also aimed to investigate the prevalence, characteristics, immunological responses, and mechanism of carriage of invasive Salmonella in the gallbladder by examining bile and tissue obtained from individuals who underwent cholecystectomy in Kathmandu. Data presented here demonstrate that S. Paratyphi A is almost as prevalent as S. Typhi in the gallbladder and that carriage may not be driven by antimicrobial resistance. Gallbladders that contained Salmonella were more likely to show evidence of acute inflammation with extensive neutrophil infiltrate. Chronic carriers were found to have dramatically elevated levels of IgG to O:2 and Vi antigens with high bactericidal activity yet low pro-inflammatory cytokine levels suggesting that Salmonella are stimulating a constant immunological response, in the form of antibody. S. Typhi may be controlling the inflammatory process through the expression of the Vi capsule in the gallbladder. Genome sequencing of S. Typhi isolated from chronic carriers were different from those S. Typhi causing acute disease. These data question the current dogmas surrounding the carriage of S. Typhi in gallbladder and predict a pivotal role of Vi capsule and gallstones in maintaining carriage. Therefore, prospectively identifying these individuals is paramount for rapid local and regional elimination. Furthermore, combining cytokine profiles and antibody levels may be a method of prospectively detecting carriers in the general population.